2009
DOI: 10.1007/s00415-009-5067-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-eye-movement sleep behavior disorder secondary to acute aseptic limbic encephalitis

Abstract: Rapid-eye-movement (REM) sleep behavior disorder (RBD) is a parasomnia characterized by complex motor activity associated with dreaming during REM sleep. RBD may be idiopathic or associated with various neurological diseases involving the brainstem. The association of RBD and limbic system impairment was unclear. We report a 46-year-old man with acute aseptic limbic encephalitis in association with RBD. The patient presented with subacute onset of anterograde/retrograde amnesia and persistent fever. Abnormal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Previous imaging studies have shown that, during REM sleep, regional cerebral blood flow is significantly increased in the pontine tegmentum, thalamic nuclei and limbic areas (26,27). This interaction within the limbic system is activated during REM sleep, suggesting that limbic system impairment may be implicated in the pathogenesis of RBD (24).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Previous imaging studies have shown that, during REM sleep, regional cerebral blood flow is significantly increased in the pontine tegmentum, thalamic nuclei and limbic areas (26,27). This interaction within the limbic system is activated during REM sleep, suggesting that limbic system impairment may be implicated in the pathogenesis of RBD (24).…”
Section: Discussionmentioning
confidence: 91%
“…Interestingly, RBD has also been reported to occur in association with damage in the limbic system without primary brainstem impairment (23)(24)(25). Previous imaging studies have shown that, during REM sleep, regional cerebral blood flow is significantly increased in the pontine tegmentum, thalamic nuclei and limbic areas (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dream enactment resolved in three of four patients treated with immunotherapy, although follow up vPSG data are not available to assess whether RWA also resolved. Additional cases of autoimmune or inflammatory encephalitis causing RBD include anti-Ma2 paraneoplastic syndrome [54] and one case of aseptic limbic encephalitis of unknown etiology [55]. All of these cases, except the last, were in individuals over age 50, reflecting the demographics of these specific types of usually paraneoplastic encephalites.…”
Section: Inflammatory and Autoimmune Conditionsmentioning
confidence: 99%
“…Limbic encephalitis, either due to voltage-gated potassium channel antibodies in a small series[81] or due to non-antibody-mediated aseptic encephalitis in a single case[82], has been associated with RBD. In over half of the patients with voltage-gated potassium channel antibodies, RBD resolved after successful immunotherapy.…”
Section: Rbd Co-morbiditiesmentioning
confidence: 99%